FORMULATION AND EVALUATION OF HERBAL TABLETS CONTAINING NYCTANTHES ARBOR-TRISTS LEAVES - CHAVAN, PRASHANT; KALSHETTI, MALLINATH; NAVINDGIKAR, NIKHIL (International Journal of Current Pharmaceutical Research, 2020)
Objective: To formulate arthritic pain relieving tablets and evaluation of tablets. Methods: The preparation of dry powder of Nyctanthes arbor-tristis leaves, 1% Acacia solution, 1%HPMC-10 solution, 1% Sodium alginate solution. The wet granulation method was used for the formulation of herbal tablets. Results: Based on the pre-formulation study, the flow property of granules was good. The physical parameters of compressed tablets color were Greenish white for F1 and F3 batch, Dark greenish-white color for F2batch. The weight variation test, hardness, thickness, friability and disintegration time for F1 batch was found to be [497±5%, 3.3±0.17, 4.00±0.005, 0.81%, 28] respectively, For F2 batch [506±5%, 3.13±0.01, 3.66±0.023, 1.43%, 25] respectively, For F3 batch [502.5±5%, 3.13±0.01, 3.96±0.001, 1.8%, 32] respectively. Conclusion: The formulated herbal tablets were used to manage arthritic pain. Based on the results, it is concluded that the formulation and evaluation of herbal tablets were good.